How Can I Become a Responsible Subject? Towards a Practice-Based Ethics of Responsiveness - Loacker, Bernadette; Muhr, Sara Louise (Journal of business ethics, 2009)
Approaches to business ethics can be roughly divided into two streams: 'codes of behavior' and 'forms of subjectification', with code-oriented approaches clearly dominating the field. Through an elaboration of poststructuralist approaches to moral philosophy, this paper questions the emphasis on codes of behaviour and, thus, the conceptions of the moral and responsible subject that are inherent in rule-based approaches. As a consequence of this critique, the concept of a practice-based 'ethics of responsiveness' in which ethics is never final but rather always 'to come', is investigated. In such an approach the ethical self is understood as being continuously constituted within power/knowledge relations. Following this line, we ask how one can become a responsible subject while also acknowledging certain limits of full responsibility. We thereby explore responsibility as a considered but unconditional openness in response to the other.